Elastin-like polypeptide incorporated thermally sensitive liposome improve antibiotic therapy against musculoskeletal bacterial pathogens. (17th February 2018) - Nigatu, Adane S.; Ashar, Harshini; Sethuraman, Sri Nandhini; Wardlow, Rachel; Maples, Danny; Malayer, Jerry; Ranjan, Ashish
Abstract: Musculoskeletal infections caused by bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa in children and adults can lead to adverse outcomes including a need for extensive surgical debridement and limb amputation. To enable targeted antimicrobial release in infected tissues, the objective of this study was to design and investigate novel elastin-like polypeptide (ELP)-based thermally sensitive liposomes in vitro . ELP biopolymers can change their phase behaviour at higher temperatures. We hypothesised that ELP-TSL will improve therapeutic efficacy by releasing antimicrobial payloads locally at higher temperatures (≥39 °C). ELP-TSL library were formulated by varying cholesterol and phospholipid composition by the thin film and extrusion method. A broad-spectrum antimicrobial (Ciprofloxacin or Cipro) was encapsulated inside the liposomes by the ammonium sulphate gradient method. Cipro release from ELP-TSLs was assessed in physiological buffers containing ∼25% serum by fluorescence spectroscopy, and efficacy against Staphylococcus aureus and Pseudomonas aeruginosa was assessed by disc diffusion and planktonic assay. Active loading of Cipro achieved an encapsulation efficiency of 40–70% in the ELP-TSL depending upon composition. ELP-TSL Cipro release was near complete at ≥39 °C; however, the release rates could be delayed by cholesterol. Triggered release of Cipro from ELP-TSL at ∼42 °C induced significant killing of S. aureus and P. aeruginosa compared to 37 °C. Our in vitro data suggest that ELP-TSL may potentially improve bacterial wound therapy in patients.